Building Digital Marketing Readiness of BUMDes and Rural MSMEs in Rancakalong Village - Eman Sulaiman; Heppy Millanyani; Vigory Gloriman Manalu; Kharisma Ellyana (PT. Berkah Digital Teknologi, 2026)
This community service program aimed to build the digital marketing readiness of BUMDes managers, women farmer groups, rural micro, small, and medium enterprise actors, local product producers, and village tourism representatives in Rancakalong Village, Sumedang Regency, West Java. The activity was conducted on 19 May 2026 and involved 21 participants. A participatory and experiential approach was applied through needs assessment, short lectures, demonstrations, smartphone-based practice, mentoring, output review, and follow-up planning. The training covered product mapping, smartphone product photography, promotional caption writing, WhatsApp Business, online marketplace preparation, product labels and packaging, and digital promotion of village tourism resources. The implementation evidence showed that the partner community had diverse economic potential, including local food, herbal beverages, coffee, processed fish products, cultural attractions, and nature-based tourism. However, marketing activities still relied mainly on personal WhatsApp accounts, word-of-mouth communication, and local customer networks. The program generated an initial mapping of priority products and tourism resources, draft promotional content, product-information components, and recommendations for developing shared digital marketing channels under BUMDes coordination. The principal practical finding was that village digital marketing readiness depends not only on access to digital devices but also on product presentation, content quality, customer-oriented communication, product legality, and institutional coordination. Continued mentoring is required to strengthen packaging, certification, marketplace management, and consistent content production.